HiCAS (Highway Context Awareness System): Information Delivery On Highway Facilities –A Preliminary Study - Wan Rani, Wan Suhaila; Mazlan, Mazwani Ayu (2012)
Context information is the information that documents the relationships of the content Information to its environment. Storage of such information can define how effective the deliverance of retrieving information. This research tries to create an on-time alert information for highway user comfort and safety measures in supporting their pleasure journey. Computer application basic inputs, such as keyboard strokes or pointing devices, supply only limited information about the surrounding highway environment, and it is not suitable for highway user to attempt the same technology. HiCAS is an attempt to reduce illiterate highway users and produce a core ideas on the approach of educating the highway user through context information technology